Cancer‐associated fibroblasts educate normal fibroblasts to facilitate cancer cell spreading and T‐cell suppression. Issue 1 (5th November 2021) - Itoh, Go; Takagane, Kurara; Fukushi, Yuma; Kuriyama, Sei; Umakoshi, Michinobu; Goto, Akiteru; Yanagihara, Kazuyoshi; Yashiro, Masakazu; Tanaka, Masamitsu
Abstract : In some tumors, a small number of cancer cells are scattered in a large fibrotic stroma. Here, we demonstrate a novel mechanism for expansion of pro‐tumor fibroblasts via cancer‐associated fibroblast (CAF)‐mediated education of normal fibroblasts (NFs). When NFs were incubated with conditioned medium from CAFs, the resulting CAF‐educated fibroblasts (CEFs) generated reactive oxygen species, which induced NF‐κB‐mediated expression of inflammatory cytokines and the extracellular matrix protein asporin (ASPN), while expression of a common CAF marker gene, α‐SMA, was not increased. ASPN further increased CEF expression of downstream molecules, including indoleamine 2, 3‐dioxygenase 1 (IDO‐1), kynureninase (KYNU), and pregnancy‐associated plasma protein‐A (PAPP‐A). These CEFs induce cytocidal effects against CD8 + T cells and IGF‐I activation in cancer cells. CEFs were generated without cancer cells by the direct mixture of NFs and CAFs in mouse xenografts, and once CEFs were generated, they sequentially educated NFs, leading to continuous generation of CEFs. In diffuse‐type gastric cancers, ASPN high /IDO‐1 high /KYNU high /α‐SMA − CEFs were located at the distal invading front. These CEFs expanded in the fibrotic stroma and caused dissemination of cancer cells. ASPN may therefore be a key molecule in facilitating tumor spreading and T‐cell suppression. Abstract : Cancer‐associated fibroblast (CAF)‐educated fibroblasts (CEFs), a newly identified source of pro‐tumor fibroblasts, were generated from normal fibroblast (NFs) by CAF‐mediated education. CAFs activated reactive oxygen species production in NFs, reprogramming them to secrete inflammatory cytokines and ASPN. ASPN further induced expression of IDO‐1, KYNU, and PAPP‐A in CEFs, leading to cancer cell dissemination, CD8 + T‐cell cytotoxicity, and activation of IGF‐I signaling in cancer cells.